Distribution of Patients with Septic Shock in Gynecology wards in A Period of Ten Years - Zahra Shahshahan; Sareh Boroumand (مجله دانشکده پزشکی اصفهان, 2011)
Introduction: Septic shock is an important and serious disease. The major aim of this research was to find demographic factors and etiology of septic shock. Methods: In this retrospective descriptive research, 400 patients with the diagnosis of septic shock who were admitted in obstetric and gynecologic words of Alzahra and Beheshti hospitals in Isfahan during ten years were evaluated. The data about age, marital status, and etiology was gathered. Results: Most of the patients were in 25-35 years and married. The most prevalent etiology of the disease was septic abortion. Most of the patients had 2 or more children and lived in town. Most of patients had history of surgical treatment plus medical treatment, had admitted for 5 days or more in hospital, were treated by 3 antibiotics and most of them lived. Conclusion: This research concluded that etiology of most of the septic shocks was septic abortion that has done illegally and in non sterile condition because of economical and social problems of having more children. This emphasized the importance of people education for avoidance of doing illegally induced abortion and septic abortion.